MODEL PEMBELAJARAN KIMIA ORGANIK TERINTEGRASI DENGAN KEMAMPUAN GENERIK SAINS - Sudarmin (Universitas Negeri Malang, 2012)
Abstract: Learning Models of Organic Chemistry Subject Integrated with Science Generic Skills. The aim of the study is to investigate how Organic Chemistry and Generic Science Skills Teaching Model can be developed for prospective chemistry teachers. This research and development study involves 79 students of Chemistry Education Department of Semarang State University. The data are collected using a test of organic chemistry concepts and generic science skills, a questionnaire, and an observation sheet and then analyzed using N-gain test. The result shows that the OCGSSM teaching model improves the prospective chemistry teachers' generic science skills in high and medium category. The high achieving student group has better comprehension of generic skills in logical consistency, observation, abstraction, symbolic language, sense of scale, and logical frame aspects than low achieving student group. Abstrak: Model Pembelajaran Kimia Organik Terintegrasi Kemampuan Generik Sains. Penelitian ini bertujuan untuk mengembangkan model pembelajaran kimia organik terintegrasi kemampuan generik sains. Penelitian dan pengembangan melibatkan 79 mahasiswa Pendidikan Kimia Jurusan Kimia Universitas Negeri Semarang. Data dikumpulkan dengan tes penguasaan konsep kimia organik terintegrasi kemampuan generik sains, angket, dan lembar observasi, dan dianalisis dengan uji N-gain. Hasilnya menunjukkan bahwa penerapan MPKOKG meningkatkan penguasaan kemampuan generik sains calon guru kimia dengan taraf pencapaian tinggi dan sedang. Mahasiswa kelompok prestasi tinggi memiliki penguasaan kemampuan generik sains konsistensi logis, pengamatan, abstraksi, bahasa simbolik, kesadaran tentang skala serta logical frame lebih baik dibandingkan kelompok prestasi rendah.